Socioeconomic strata as a predictor factor for consistent condom use among adolescents - Ramiro Caballero Hoyos; Alberto Villaseñor Sierra
INTRODUCTION: Socioeconomic level plays an important role in health inequalities. In Mexico, the highest prevalence of AIDS cases is among individuals of lower socioeconomic level. The purpose of the study was to describe the socioeconomic level (adjusted for psychosocial, situational and demographic variables) as a predictor factor for the consistent condom use among adolescents of Guadalajara, Mexico. METHODS: A sample of 1,410 adolescents, aged 15 to 19 years, drawn from a previous survey stratified by age, gender and socioeconomic strata was included in the study. Analysis was performed in 251 adolescents who reported sexual activity. Statistical analysis was performed using Chi-square, t-test, ANOVA, and logistic regression. RESULTS: The frequency of consistent condom use was 30.7% and there was a prevalence of irregular use. The highest social level was the main predictor (OR= 11.1, CI 95%=2.6-47.6). Others significant predictors were male gender, peer support and better knowledge about HIV/AIDS. CONCLUSION: Socioeconomic level is an important predictor factor for consistent condom use.